Effect of Storage on Bean and Cup Qualities in Robusta Coffees under Different Processing Methods - Nakendo, S; Musoli, P C; Kananura, E; Wagoire, W W (Journal of Postharvest Technology, 2016)
Quality is the most appreciated characteristic at the international coffee trade and  consumers continue to demand for it. However, a number of production factors,  including postharvest handling mainly processing methods and storage are  implicated in determining the final bean and cup quality. Here, beans derived from  different processing methods (naturals, pulped naturals and fully washed coffees)  strictly under the same storage conditions, were appraised for bean and cup quality  profiles. The outcome in this trial indicates that fully washed Robusta coffees had  the best bean and cup quality profiles
Keywords: Robust Coffee; Processing; Storage; Quality Postharvest